Multimedia and Its Role in The Modern World - Baxreddinova, Ganixanova Madina; Kamiljanovna, Muhammedova Nargiza; Normuminovich, Mirzakulov Ilxom (International Journal of Psychosocial Rehabilitation, 2020)
Multimedia are multiple information environments-interfaces that provide input/output of information of different types to the computer, computer creation, processing and display of information of different levels and structures for perception by different human senses at the same time. Multimedia is a set of information media-channels, each of which has its own specific form corresponding to its level and purpose. The main environments are ordered in ascending order, as follows: • binary environments that include processor instructions, program and data binaries • contact environment, which is a tactile, strain, electric, capacitive and other touch environment, used to input mechanical code and other spatial-dependent information; • text environments, which are text data for people, program texts for interpreters, other text information; • audio streams, which are sound files, series of digitized sound, sets of musical audio data and other types of digital sound; • graphical environments, which are files of drawings, photographs and other two-dimensional graphical information; • video streams, which are video files, series of dynamic graphic information; • virtual reality, which is an interactive 3D video